Mothers' Knowledge about Dehydration due to Diarrhea in Children under 5 Years - Khamees 8. Obeid (Iraqi National Journal of Nursing Specialties, 2023)
Objective: The study aims to assess mothers' knowledge about their children less than 5 years with dehydrationdue to diarrhea and to find the relationships between the mothers' knowledge and their demographiccharacteristics.Methodology: A descriptive study was carried out in 2 pediatric teaching hospitals (Child's Center PediatricTeaching Hospital and Children Welfare Pediatric Teaching hospital in the city of Baghdad from the lstNovember 2007 to the lst May 2008. A purposive "non probability" sample of (50) mothers. Tliese mothers areadmitted to hospitals with their children. The data were collected through using constructed questiormaire whichcomprises (52) items and filled by using interview technique. The reliability of the questiormaire was determinedthroughapilotstudyandthevaliditythroughapanelofexperts.Thedatawereanalyzedthroughtheapplicationof descriptive statistic frequency, percentage, and the application of inferential statistical procedures, whichinclude Pearson correlation coefficient and chi-square.Results: The results of the study indicated that (30%) of mothers age between the ages of (31-35) years and thehighest proportion of sample (24%) their level of education is (primary school), and half of the sample (50%)were government employee, and (40%) of the sample bad inadequate income. The results indicated that (56%)and (52%) of the mothers has fair knowledge about general information of dehydration, and the responsibility ofthe mother towards child with dehydration respectively. In general, the results indicated that more than half ofthe sample had fair knowledge (52%) to all aspects of dehydration. The finding have approved that there is asignificant relationship between mothers' knowledge and demographic characteristics such as age, educationallevel, occupation of the mother and family income.Recommendations:The study recommended that mothers' knowledge should be improved about the dangers of diarrhea anddehydration.